An analysis of the parliamentary opposition to the national government's handling of the international situation, November 1935 - May 1940 - Giles, Donald (1976)
The following pages are devoted to Members of Parliament - Labourites, Liberals, Nationals, Independents - who expressed dissent at the National Government's handling of foreign and defence affairs. Each of these groups was studied separately, but care was taken to view the Opposition in toto, so that similarities of view or approach were ascertained. Any efforts made to effect a united opposition were traced, as were the inter-party movements that originated in these years. Finally, research was undertaken to discover what factors - sociological, economic, electoral - differentiated dissidents from loyalists in the governing coalition or rival factions within the Opposition Parties. It appeared that the Government's opponents, despite divergencies, began to move towards a common goal of limited collective security. Nevertheless, so divided were they by rival creeds and calculations that little co-operation was affected until the outbreak of war. Separately, however the dissidents achieved little, primarily because each group was crippled by a lack of cohesiveness within its own ranks. The end result was that the Government had a freer hand than it would otherwise have had. The counsel offered by the Opposition looked to the fortification of peace to deter the dictators or to overawe them if aggression occurred. Although insufficient thought had been given to how the allies would have fared in the event of war, the grand alliance policy was - and was recognised by the public to be - an alternative to appeasement. As to the flimsy dividing line between both Coalition loyalists and dissidents and groupings within the opposition Parties it would seem that the only significant difference was that of aggregate experience. In effect, dissent or specialism in foreign or defence matters was found to be primarily connected with members being placed in close relations with overseas interests or serving either in the Forces or in a related department.